The effects of personal income tax reform on employees' taxable income in Uganda - Maria Jouste; Tina Kaidu Barugahara; Joseph Okello Ayo; Jukka Pirttilä; Pia Rattenhuber (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
We evaluate a major personal income tax reform in Uganda that came into effect in 2012-13. The reform increased the tax-free lower threshold, increased tax rates for higher incomes, and introduced an additional highest tax band. Using the universe of pay-as-you-earn administrative data submitted by employers in the formal sector, we analyse the impact on taxable income of the introduction of the additional top tax band. Our results indicate that the elasticity of taxable income in Uganda is larger than in previous results from developed countries. Overall, the additional revenue generated from the introduction of the additional top tax band by far offset the revenues lost from the decreased revenues from employees with medium to lower taxable incomes, despite the large elasticity of taxable income at the top. We contribute to the very scarce literature on the effects of personal income tax reform on employees' income in a low-income country in Africa.
Keywords: C31; H24; O23; 330; personal income tax; Uganda; administrative data; tax reform